How and why people change : foundations of psychological therapy - Evans, Ian M., 1944- (Oxford University Press, 2013)
This resource revists many of the fundamental principles of behaviour change in order to deconstruct what it is we try to achieve in psychological therapies. All of the conditions that impact people when seeking therapy are brought together in one cohesive framework: assumptions of learning, motivation, approach and avoidance, barriers to change, personality dynamics, and the way that individual behavioural repertoires are inter-related.